Tenderness of the skin after chemical stimulation of underlying temporal and thoracolumbar fasciae reveals somatosensory crosstalk between superficial and deep tissues - Magerl, Walter; Thalacker, Emanuela; Vogel, Simon; Schleip, Robert; Klein, Thomas; Treede, Rolf-Detlef; Schilder, Andreas (Life, 2021)
Musculoskeletal pain is often associated with pain referred to adjacent areas or skin. So far, no study has analyzed the somatosensory changes of the skin after the stimulation of different underlying fasciae. The current study aimed to investigate heterotopic somatosensory crosstalk between deep tissue (muscle or fascia) and superficial tissue (skin) using two established models of deep tissue pain (namely focal high frequency electrical stimulation (HFS) (100 pulses of constant current electrical stimulation at 10× detection threshold) or the injection of hypertonic saline in stimulus locations as verified using ultrasound). In a methodological pilot experiment in the TLF, different injection volumes of hypertonic saline (50-800 µL) revealed that small injection volumes were most suitable, as they elicited sufficient pain but avoided the complication of the numbing pinprick sensitivity encountered after the injection of a very large volume (800 µL), particularly following muscle injections. The testing of fascia at different body sites revealed that 100 µL of hypertonic saline in the temporal fascia and TLF elicited significant pinprick hyperalgesia in the overlying skin (-26.2% and -23.5% adjusted threshold reduction, p < 0.001 and p < 0.05, respectively), but not the trapezius fascia or iliotibial band. Notably, both estimates of hyperalgesia were significantly correlated (r = 0.61, p < 0.005). Comprehensive somatosensory testing (DFNS standard) revealed that no test parameter was changed significantly following electrical HFS. The experiments demonstrated that fascia stimulation at a sufficient stimulus intensity elicited significant across-tissue facilitation to pinprick stimulation (referred hyperalgesia), a hallmark sign of nociceptive central sensitization.
Gesehen am 28.09.2021